Anti-inflammatory sesquiterpene and triterpene acids from Mesona procumbens Hemsley - Huang, Hung-Tse; Lo, I-Wen; Liao, Geng-You; Lin, Yu-Chi; Shen, Yuh-Chiang; Huang, Hui-Chi; Li, Tsung-Lin; Lee, Kung-Ta; Kuo, Yao-Haur; Liaw, Chia-Ching (Frontiers in Chemistry, 2022)
Mesona procumbens Hemesley is a plant conventionally processed to provide popular food materials and herbal medicines in Asia. In this study, six triterpene acids, including five new ones (mesonaic acids D-H, 1‒5), and one proximadiol-type sesquiterpene (7) were isolated from the methanolic extract of the air-dried M. procumbens. Chemical structures of 1‒7 were established by spectroscopic methods, especially 2D NMR techniques (1H‒1H COSY, HSQC, HMBC, and NOESY) and HRESIMS. Concerning their biological activities, compounds 1, 2, 6, and 7 were examined manifesting high inhibition toward the pro-inflammatory NO production with EC50 values ranging from 12.88 to 21.21 µM, outrunning the positive control quercetin (24.12 µM). The mesoeudesmol B (7) identified from M. procumbens is the very first example, which exhibited high anti-inflammatory activity diminishing the level of the lipopolysaccharide-induced NO in RAW264.7 macrophage cells, thereby suppressing the secretion of pro-inflammatory cytokines TNF-α and IL-6 and the level of two critical downstream inflammatory mediators iNOS and COX-2.